Asy’ariyah; Sejarah dan Pokok Ajarannya Serta Keterkaitannya Dengan Mu’tazilah - Qorina, Ulfa; Amri, Muhammad; Santalia, Indo (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Al-Asy’ari is one of the theological schools in Islam that emerged in the 9th century A.D. This school was founded by Abu al-Hasan al-Asy'ari as a response to the Mu'tazilah who prioritized reason in understanding religious teachings. Asharite history began as a movement to affirm elements of faith without neglecting revelation. The Asharites emphasized the principles of faith, including belief in the attributes of Allah, destiny, and the existence of the Qur'an as an uncreated kalamullah. This school rejects some Mu'tazilah concepts such as the affirmation of the absolute justice of God and the ability of the human intellect to attain religious knowledge without the aid of revelation. The al-Asy’ari association with the Mu'tazilah reflects a theological debate in Islamic history, in which the asy’ari tried to restore the primacy of revelation and tradition, while the Mu'tazilah supported reason as the primary means of understanding religion. These differences influenced the development of Islamic thought and contributed to the development of Islamic thought.